A Critical Examination of Game Theory as Applied to Conflict and Negotiation - Merle van den Berg (Communicare, 2022)
MANY scholars and politicians have sug gested negotiation as a solution for South Africa's problems. Although the subject of negotiation has been eclectic in the absorp tion of Insights from other disciplines, it is only fairly recently that communicologists have become interested in the topic. Today there are various theoretical approaches underlying the study of negotiation. The Theory of Games (or Game Theory) is one of the earlier approaches -one however which is still popular in some quarters. This article overviews the literature on Game Theory as applied to conflict and negotiation, and the writer concludes that though useful initially, it is no longer suitable for the study of real-life conflict and negotia tion situations. The communicologist will have to find a less behaviouristic approach if he hopes to understand (and apply) the com plexities of negotiation. Only then can we begin to talk of solutions